Subcutaneous auto-administration of trastuzumab following therapeutic education: A case report. (September 2019) - Deppenweiler, Marine; Debled, Marc; Robquin, Jean-Luc; Lortal-Canguilhem, Barbara
Trastuzumab is a monoclonal antibody used to treat human epidermal growth receptor 2 positive (HER2+) breast cancers either by itself or in combination with other chemotherapy medication. Marketing authorization was granted for a subcutaneous form of the antibody in 2014. In this case report, we discuss our experience with a patient who took part in a therapeutic education program on self-administration of trastuzumab. We demonstrate that these types of self-administered injections are not only possible but also are toxicity-free. Based on the tolerance data and our patient's experience, we propose that the current regulations be relaxed regarding the availability of trastuzumab subcutaneous form in order to develop a cheaper "city scheme, " i.e. self-administered injections.